2016
DOI: 10.1080/10610278.2016.1158408
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular dimeric structures of pyrazole-containing meso-oxo carbaphlorin analogues

Abstract: Synthesis and properties of a novel meso-oxo carbaphlorin analogue embedded with an N-free pyrazole moiety are described. The N-benzyl precursor was prepared by a [3 + 1]-MacDonald condensation of N-benzyl pyrazole dialdehyde and β-alkyl-substituted tripyrrane dicarboxylic acid and subsequent oxidation by ferric chloride. Upon deprotection of the benzyl group, the resulting N-free oxophlorin analogue formed a unique supramolecular dimer through mutual hydrogen bonding interactions between the pyrazole NH and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…In a recent paper, a TFA-promoted condensation of N -benzylpyrazole dialdehyde 212d with tripyrrane 36a in methanol–dichloromethane was reported . Following neutralization with triethylamine and oxidation with DDQ, oxophlorin analogue 215d was isolated in 12% yield (Scheme ).…”
Section: Pyrazole-containing Porphyrinoidsmentioning
confidence: 87%
See 2 more Smart Citations
“…In a recent paper, a TFA-promoted condensation of N -benzylpyrazole dialdehyde 212d with tripyrrane 36a in methanol–dichloromethane was reported . Following neutralization with triethylamine and oxidation with DDQ, oxophlorin analogue 215d was isolated in 12% yield (Scheme ).…”
Section: Pyrazole-containing Porphyrinoidsmentioning
confidence: 87%
“…Single-crystal XRD analysis showed that the porphyrinoid is planar and also demonstrated that a “head-to-head” dimer structure was present. Evidence for the formation of the dimer in solution was also presented Scheme ).…”
Section: Pyrazole-containing Porphyrinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such approaches provide easy access to effectively obtain 1,3,5-trisubstituted pyrazoles with definite types of substituents. That approach is specifically topical due to the yearly increasing significance of the pyrazole sequence chemical variety for pharmaceutics, coordination chemistry, supramolecular chemistry, liquid crystals, polymers, and agricultural chemistry . Therefore, there has been much progress on development of common synthesis methods and for the functionalization of polysubstituted pyrazoles …”
Section: Introductionmentioning
confidence: 99%
“…Pyrazoles are very important functional moieties having extensive applications in pharmaceuticals, 1 agriculture, 2 supramolecular chemistry, 3 polymers, 4 liquid crystals, 5 ligands in catalysis 6 and many others. Despite the intricacy in N–N bond formations, these are widely present in nature 7 such as in withasomnine, pyrazofurin, formycin A and B, nostocine A, fluviol A–E, and pyrazole-3(5)-carboxylic acid and show remarkable biological potential.…”
Section: Introductionmentioning
confidence: 99%